Study and Marketing Strategy to Increase Service Sales At PT. Sunlife Financial Indonesia Using SWOT Method - Yani Dahliani; Helmi Agus Salim (ABM: International Journal of Administration, Business and Management, 2023)
From the results of calculating the EFAS and IFAS matrices in the position matrix, the appropriate strategy was carried out by PT. Sunlife Financial Indonesia is a diversification strategy, namely increasing the products / services offered and market development. These results were obtained from internal factors, namely 2.6, which was obtained from the total sum of the company's strength and weakness factor ratings, and from the company's external factors, namely 2.85, which was obtained from the total sum of opportunity and threat factors. And it was found that external factors were higher than internal factors, this was because PT. Sunlife Financial Indonesia has a big threat to its business, where competition from similar businesses continues to increase, but PT. Sunlife Financial Indonesia can provide the strength it has to take advantage of existing opportunities.